PERSEPSI MASYARAKAT TERHADAP PROGRAM PENGELOLAAN SAMPAH SECARA REDUCE, REUSE, RECYCLE (3R) DI KELURAHAN MANEMBO-NEMBO TENGAH KECAMATAN MATUARI KOTA BITUNG - Mario Rinaldi Malee; Benu Olfie Olfie L.S; Welson M. Wangke (AGRI-SOSIOEKONOMI, 2016)
Perceptions in relation to the environment, namely as the process where individuals organize and interpret their sensory impressions in order to give meaning to the environment. With the perception of the attitude that it will form a stable tendency to act a certain way in certain situations. Research on the public perception is very important because by knowing that perception would help prevent the arising problems. The purpose of this research is to determine public perception to Trash Processing Program by using 3R method viewed from aspects Socialization, facilities providing, and sorting, composting, and recycling by using instrument Likert scale. This research has been carried out for three months, from February until March 2016 from preparation till the preparation of research reports. Research located in the Manembo-nembo Tengah Sub District Matuari district Bitung City..This research using primary data and secondary data. Primary data obtained from 68 respondents by using questionnaires. While Secondary data obtained from Dinas Kebersihan and Menembo-nembo tengah office. Sampling method used in this research is purposive sampling. This research shows that public perception to trash processing socialization program with 3R still neutral, because of the low socialization from local govern, while public perception to facilities and infrastructure providing program is positive. For public perception to sorting, composting, and trash recycling is positive. So that most of public have positive perception to trash processing socialization program with 3R.Keywords: Public Perception, Solid Waste Managemeny, Manembo-nembo Tengah, Bitung City.